Legal Protection for Carrying Out Anesthesia Without an Anesthetist For Anesthetists in Hospitals Prima Inti Medika North Aceh - Muliadi; Fauzan; Risdawati, Irsyam (Ilomata International Journal of Social Science, 2025)
Introduction: This study aims to analyze the Standard Operating Procedure (SOP) for anesthesia, the implementation of anesthesia procedures in the operating room without an anesthetist, and the legal protection for anesthesia practitioners in such cases. This issue highlights the importance of policy implementation and its impact on patient safety and legal accountability. Methods: The research utilized an analytical-qualitative method, which is descriptive in nature and emphasizes analysis. Data were collected through interviews with specialist anesthetists and stylists at Prima Inti Medika Hospital. This approach allowed for an in-depth understanding of the policy implementation and related challenges. Results: The findings reveal that the delegation of authority for anesthesia procedures and communication among related teams are implemented effectively. However, challenges were identified, including issues with policy standards, resource adequacy, and the disposition or attitudes of implementers. These challenges have hindered the optimal implementation of delegation policies, thereby impacting legal protection for anesthesia practitioners. Conclusion: The study emphasizes the critical need for effective policy implementation regarding the delegation of authority in anesthesia services. Hospital management must actively monitor and evaluate the implementation process while ensuring administrative compliance. Supporting the development and competence of health workers, particularly anesthesia administrators, is essential to achieving quality services that prioritize patient and staff safety.